Reconstructing the Islamic Religious Education Curriculum in the Era of Artificial Intelligence: Strengthening the Human Dimension in Digital Learning - Dhevin MQ Agus Puspita W; Khotimah Suryani; Syihabuddin Qulyubi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) in the last decade has brought fundamental changes to the global educational landscape, including Islamic Religious Education (PAI). On one hand, AI offers extraordinary transformative potential: adaptive learning, content personalization, and assessment efficiency. On the other hand, excessive technological dominance risks eroding the human dimension in education the soul, values, and teacher-student relationship that form the heart of PAI. This article critically examines the need to reconstruct the PAI curriculum to remain relevant in the AI era without losing its essence as humanizing education. Through a library research approach with multidisciplinary literature analysis Islamic educational philosophy, educational technology, and curriculum studies this research formulates an integrative human value based PAI curriculum reconstruction framework. The findings show that PAI curriculum reconstruction in the AI era must rest on three pillars: strengthening spiritual-ethical competencies as a foundation, critical-reflective technology literacy, and revitalization of humanistic pedagogical relationships.